A Combined Distal Tibial Turn-up Plasty and Intercalary Calcaneal Osteocutaneous Fillet Flap for Salvage of a Transtibial Amputation: A Case Report. Issue 4 (October 2017) - Wade, Sean M.; Harrington, Colin; Fleming, Mark; Potter, Benjamin K.
Abstract : Case: This case demonstrates the successful attempt at a combined distal tibial turn-up plasty and intercalary calcaneal osteocutaneous fillet flap to increase functional limb length in order to salvage a transtibial amputation following a high-energy blast injury. Conclusion: A transtibial amputation is preferred over more proximal levels of amputation because of the decreased energy expenditure that is required for ambulation. In cases where there is not enough viable tibia to allow for a transtibial level of amputation, combining a calcaneal osteocutaneous fillet flap with a distal tibial turn-up plasty can be utilized to optimize residual limb length for a transtibial amputation.